A REFORMA PSIQUIÁTRICA - UM ESTUDO PARCIAL ACERCA DA PRODUÇÃO CIENTÍFICA DA TEMÁTICA - Luciane Prado Kantorski (Universidade Federal de Goias, 2001)
This work describes a theoretical reflection about the theme of the psychiatric reform in its theorics and practicals conceptions. For this objective was made a partial analysis of the scientific production about the psychiatric reform, taking like reference the abstracts published in the LILACS and in the programs and communications on the Congresso Brasileiro de Enfermagem, since 1987. For the treatment of the raised data was elected like analytical category the exclusion and like empirical category the disinstitutionalization. It was looked for the production of a vision about the psychiatric reform that approximate the health staff to the present reflections regarding new forms for to think and to act towards the craziness problematic.